Cloud Computing and Security - Mansoor Bigdeloo; Mostafa Ramezani; Abolfazl Rafat (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Following personal computers, one of the most important innovations in the IT industry is cloud computing ad it appeared with the advent of a major revolution in the IT industry. Cloud computing allows organizations to reduce or increase their resources according to operational needs. In fact, cloud computing means the development and deployment of computer technology to provide computational resources through the Internet. Cloud computing is an information space architecture that allows network-based and demand-driven access to a large array of common computing resources at very low cost, high innovation, and development, as well as without spatial and temporal constraints. Cloud computing is one of the most important and powerful tools for securing and managing massive data and allocating resources in the infinity of the Internet.